The Effect of Planting Media Composition and Liquid Organic Fertilizer on the Growth and Yield of Celery (Apium graveolens L.) in Verticulture - Wardana, I Gede Krisna; Kartini, Ni Luh; Sardiana, I Ketut (International Journal of Biosciences and Biotechnology; Vol 12 No 1 (2024): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2024.v12.i01.p03, 2025)
Verticulture system cultivation has the advantage of saving land, water, fertilizer and planting media. This research was carried out in Banjar Dinas Blumbang Kelod, Blumbang Village, Tabanan Regency, Bali, Indonesia, using a factorial randomized block design. The first factorial was the composition of the planting media with 4 treatmens, namely, M0: Soil (100 %), M1: Soil + Vermicompost + Sand (50%: 20%: 30 %), M2: Soil + Vermicompost + Sand (50%: 30 %: 20%) and M3: Soil + Vermicompost + Sand (20%: 50%: 30%). The second factor was the provision of liquid organic fertilizer which consists of 4 treatments, namely: P0: 10 ml/plant, P1: 20 ml/plant, P2: 30 ml/plant and P3: 40 ml/plant. The composition of the planting media provided significantly different plant height in the M2 treatment with the highest values of 24.17 cm and 33.08 cm. At 42 and 70 day after planting (dap) shows values of 79.92 strands and 239.25 strands. The fresh weight was significantly different at 62.42 g at 80 days after planting. The fresh weight of the plants above ground at 112.83 g. At 80 dap, the total dry weight of the plants was 28.42 g. The effect of liquid organic fertilizer was significantly different in the P0 treatment with plant height of 24.50 cm. The interaction at 70 dap and 80 dap of the M2P2 treatment with the number of leaves being 259.67 and 271.33. The highest value of p population microorganisms in the M2 P1 treatment amounted to 100.00 and the lowest was shown by the M0P3 treatment at 39.33, with an increase of 60.67%.